ANALYSIS OF TRIAGE CODE AND DIAGNOSIS DISTRIBUTIONS OF PATIENTS ARRIVING VIA 112 EMERGENCY SERVICES - Emre Kahveci; Zehra Aldemir; Mazlum Aslan; Berivan Ağaoğlu; Ejder Saylav Bora (Izmir Katip Celebi University Faculty of Medicine, 2026)
ABSTRACT Objective: The aim of this study is to interpret the use of 112 emergency medical services by revealing the demographic characteristics, triage code and diagnosis distributions, and outcomes of patients who arrived at a training and research hospital via 112. Method: This study retrospectively examined patients who arrived at the emergency department of İKÇÜ Atatürk Training and Research Hospital by ambulance between January 1 and December 31, 2024, using the hospital information system. Patients with incomplete or incorrectly completed medical reports were excluded from the study. Results: Of the 321 patients examined, 55.45% were male. 47.98% of the patients were over 65 years old. The yellow triage code accounted for the largest share with 51.09%. The most frequent reason for admission was trauma (21.81%; n=70). Following trauma, cardiovascular and neurological system causes were the next most common. 47.98% of the patients were discharged after treatment without requiring hospitalization. Conclusion: The 112 emergency medical system is frequently used unnecessarily in our country. Unnecessary ambulance use was found to be less frequent in our research area compared to the reviewed literature. The vast majority of ambulance use and mortality reasons stem from preventable health problems. Various sanctions can be considered to prevent unnecessary ambulance use.